Facilities available in the medicine shops in Chittagong city corporation area: A cross- sectional study conducted in Bangladesh - Jakaria, Md; Sayeed, Mohammed Aktar (Bangladesh Journal of Medical Science, 2019)
Background: The aim of this was to inspect the facilities available in the medicine shops and their impacts on quality medicines and health services to be found in the Chittagong City Corporation of Bangladesh. Method: This cross-sectional study was conducted from December 2015 to February 2016. A well-designed standard protocol developed by the project supervisor. Different information was collected from the medicine shops. Results: Among the total 190 studied medicine shops, pharmacist and physician were available in 99 (52%) and 51 (27%) shops, respectively. A-grade pharmacist was available in four(04) shops. However, no air conditioner was found in 14 shops, while a refrigerator was not found in 15 shops but these shops were facing sun rays from the east side. In addition, four (04) and five (05) shops were not used the air conditioner and refrigerator, respectively but they were facing sun rays from the west side. Conclusion: Facilities in the medicine shops in this city were good, however, we think the responsible person should be more aware to ensure proper retail pharmacy practices. Bangladesh Journal of Medical Science Vol.18(4) 2019 p.760-763